Analisis Kinerja Keuangan Pada Perusahaan Umum Daerah Air Minum (Perumdam) Tirta Mayang Kota Jambi - Ega Kurniasih; Rita Friyani; Riski Hernando (LPPM UBP, 2023)
This study aims to find out how the financial performance of the Tirta Mayang Regional Drinking Water Company (PERUMDAM) Jambi City uses solvency, profitability, activity and liquidity ratios. This research uses descriptive research type and quantitative research characteristics. The population used in this study is the financial statements of the Tirta Mayang Public Water Company (PERUMDAM), Jambi City. Based on the results of the discussion it can be concluded that 1). The financial performance of PERUMDAM Tirta Mayang City of Jambi as assessed by the analysis of the liquidity ratio has increased every year which illustrates that the company is in very good condition. 2). The financial performance of PERUMDAM Tirta Mayang City of Jambi as assessed by solvency ratio analysis stated that the company's financial performance was not good or less effective so it needed to be improved. 3). The financial performance of PERUMDAM Tirta Mayang, City of Jambi, assessed by analysis of profitability ratios, stated that the company's financial performance was not good or less effective, so it needed to be improved. 4). The financial performance of PERUMDAM Tirta Mayang City of Jambi assessed by activity ratio analysis stated that the company's financial performance was not good or less effective so it needed to be improved. Key Words: Liquidity Ratio, Solvency Ratio, Profitability Ratio, And Activity Ratio